Upgrading biogas by membrane contactor separation - Rahmat, Nopia; Mohamad, Hafiz; Mel, Maizirwan (Penerbit Akademia Baru, 2018)
Biogas consists of mixture of gases, among which methane and carbon dioxide are major composition. The upgrading biogas involves the process of separation methane from other mixture of gases in raw biogas especially carbon dioxide to get high yield of biomethane. The present of other mixture of gases drops the calorific value of biogas and it reduces the quality of biogas. In this research, the membrane contactor separation was used to upgrade the biogas concentration. The main purpose of the research is to maximize the composition of methane in biomethane produced after separation process conducted by determining the condition or parameter during separation process. The parameter involved was inlet pressure which pressure above 2.5 bar had promising the higher biomethane composition obtained, as the inlet pressure increases, the composition of biomethane obtained increases. At inlet pressure 2.5 bar, the composition of methane can achieve 71.2% with 21.1% of carbon dioxide composition at permeate stream. Besides, the type of adsorbents used affect the efficiency of membrane contactor. The adsorbents used for this experiment were molecular sieve 13X and granular activated carbon which 2.5 bars inlet pressure was applied. The molecular sieve had better performance in the separation of methane and carbon dioxide with 64.7% of methane composition at peak compared to the granular activated carbon with 60.0% of methane composition at peak. The operating parameter and type of adsorbents used influenced the performance of membrane as well as the quality of biomethane produced during separation process. As conclusion, process parameter and adsorbents type are crucial components in membrane contactor separation process to upgrade biogas.